Relevance of Educational Contribution Of Jiddu Krishnamurti In The Present System Of Education (International Journal of Scientific Research and Management (IJSRM), 2018)
Jiddu .Kishnamurti’s influence on the educational ethos of alternative Indian education is immense. Although he was not an educator in the narrow sense of the term, he worked incessantly in the field of education. He is appropriately described as a ’revolutionary teacher who worked tirelessly to awaken people’. He felt that if people could be awakened to their conditioning of nationality, religion and desires, which inevitably leads to conflicts, they might bring a total change in their lives. His concern for ’good society’ found expression in the establishment of schools in India and abroad. Krishnamurti’s approach to education was highly original and unconventional for them education should aim at the inner transformation and liberation of the human being. The function of education is to help a person from childhood not to imitate anybody, but to be true to his/her own self all the time. Freedom is the basic motto of Education. Krishnamurti emphasised the relationship between Education and society and said that it’s only after evolving a sensible policy of "right’ education that we can look forward to the formation of better society. In today’s context his views on education are of paramount significance. J. Krishnamurti has been an eminent philosopher and educationist of India. The impact of his philosophy on the educational ethos of alternative Indian education has been of an unquantifiable quality, although this is often not visible in the formal components of secondary school education. Krishnamurti was not an educator in the narrow or formal sense of the term, as he had no formal qualifications to either propagate or promote educational goals or establish educational institutions. Krishnamurti has been described as a revolutionary teacher who worked tirelessly to awaken people to awaken their intelligence, to awaken their sense of responsibility, to awaken aflame of discontent and this commitment to awaken the consciousness of people was undoubtedly based on a ’strong moral passion’